Spiritual Education for Children as A Shared Responsibility Between Parents and The Church - Sitanggang, Murni Hermawaty (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
Parents must nurture their children from their earliest days to know God personally. However, some parents sometimes do not realize this and neglect their responsibility. Thus, this study explores how parents and the church should develop a mutual partnership in children’s spiritual education. The author used a qualitative method with a literature approach to investigate the problem and propose suggestions. The conclusion was that the parent is the primary responsible party in educating children. But, they can not do this task independently without the church's help. Since relying on Sunday School as part of the church’s responsibility for teaching children alone is not enough, the church could help them by providing training that educates parents to do their parental responsibilities. And to ensure that the education at home will overlap with church teaching, Sunday School teachers and parents as partners should develop mutual respect and communication. If everyone involved in children's ministry, directly or indirectly, could cultivate this joint responsibility, it would help children grow in fear of God and be better people. As the future generation, improving the quality of our ministry for children will eventually create a better church, now and later.